Artificial Intelligence of Internet of Things (AIoT) Technology-based Law Enforcement Process - Tarigan, Muhammad Iqbal; Sitepu, Noviyanti Wulandari (Internet of Things and Artificial Intelligence Journal, 2023)
Technological developments are increasingly developing in all fields, unstoppable in the area of law and the role of this IoT technology in solving legal problems, considering Society 5.0, which focuses on building a humane and prosperous society, especially people in Indonesia. And the role of IoT on the legal side is expected to be the answer for an appropriate and fair law enforcement process. IoT Technology collaboration with all sectors of human life, for example, legal, social and economic, as well as natural resource factors and human resources, are still needed. IoT is expected to be a tool to achieve a level of accuracy, real-time, fast, and stability. In the era of Society 5.0, all aspects were asked to be fast so as not to be left behind in any sector; the ability factor of the human being, namely human resources, also determines whether a matter or case can be appropriately resolved. This article is one of the review articles on the role of IoT in law enforcement. Some parameters within the Internet of Things form Artificial Intelligence, Deep Learning, Big Data, and Machine Learning. Solutions with AI can be seen in the lie detection system.